2010
DOI: 10.1104/pp.110.155655
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Boron Mobility in Wheat and Canola Phloem    

Abstract: Low-molecular-weight borate complexes were isolated from canola (Brassica napus) and wheat (Triticum aestivum) phloem exudates, as well as the cytoplasm of the fresh-water alga Chara corallina, and identified using matrix-assisted laser desorption/ ionization time-of-flight mass spectrometry. Phloem exudate was collected from field-grown canola inflorescence stalks by shallow incision, while wheat phloem exudate was collected by aphid stylectomy. Chara cytoplasm was collected by careful manual separation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 28 publications
4
34
0
Order By: Relevance
“…A similar mechanism was also described for the B transporter BOR1 (Takano et al, 2005). It has also been reported that some B-binding membrane proteins are localized in microdomains (Wimmer et al, 2009), and B was identified as a bissucrose borate complex in the phloem of wheat and canola (Stangoulis et al, 2010). However, whether SUT1 and BOR1 are coregulated has not yet been determined.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…A similar mechanism was also described for the B transporter BOR1 (Takano et al, 2005). It has also been reported that some B-binding membrane proteins are localized in microdomains (Wimmer et al, 2009), and B was identified as a bissucrose borate complex in the phloem of wheat and canola (Stangoulis et al, 2010). However, whether SUT1 and BOR1 are coregulated has not yet been determined.…”
Section: Discussionsupporting
confidence: 55%
“…SUT1 belongs to the first system and SUT4 to the second one (Weise et al, 2000). Interestingly, the long-distance transport of sucrose and B both occurred through the plant phloem, and Stangoulis et al (2010) revealed that B exists as bis-sucrose borate complex in phloem exudates of wheat. Wimmer et al (2009) had isolated and identified some boron-binding membrane-associated proteins in roots of Arabidopsis thaliana and Zea mays.…”
Section: Introductionmentioning
confidence: 99%
“…Despite that a direct mechanistic association has been established between translocation of polyols and B mobility, a certain degree of B remobilization may be observed in plant species that lack polyols in the phloem or vice-versa (Lehto et al, 2004). In addition, sucrose translocation could itself support some B mobility according to recent reports (Stangoulis et al, 2010). Reports on B mobility in solanaceaous species are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that B remobilization is more obvious in species that translocate polyols in the phloem, species that do not belong to the above group (i.e., they predominantly translocate sucrose) also show an appreciable level of B mobility (Shelp, 1988;Liu et al, 1993;Marentes et al, 1997;Stangoulis et al, 2001;Lehto et al, 2004). Recently (Stangoulis et al, 2010), a putative bis-sucrose borate complex has been identified in the phloem sap of canola and wheat. This result extends the possibility of B phloem mobility in plant species that translocate sucrose.…”
Section: Introductionmentioning
confidence: 99%
“…Both techniques could be used in future work exploring the elemental, metabolite and protein composition of phloem exudate collected from single stylets. This will help expand on the current body of work in phloem proteomics [10,18], micronutrient transport [19] and phloem metabolomics [20]. …”
Section: Discussionmentioning
confidence: 99%